The influence of psychosocial factors on positive student development (PSD) among community college students in Malaysia - Mohamed, Nor Hidayah; Hamzah, Siti Raba'ah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Psychosocial factors influence positive student development at Malaysian community colleges nationwide. Such factors which include both internal and external assets have been found to impact the development of students. The Ecology of Human Development Theory by Bronfenbrenner and the Developmental Assets Framework by Benson provide the foundation for this area of study. Internal assets in this research include resiliency, religiosity, knowledge, skills, and social entrepreneurship. Meanwhile, external assets refer to the role of parents and peers as well as structured programmes aimed at the development of students. Future research could provide a more definitive theoretical statement of influence of psychosocial factors on positive student development.